Equitable Healthcare for Indigenous Peoples: Development of the "Sharing Circle" Web Site to Provide a Culturally Safe Method to Communicate Wound, Ostomy, and Continence Information and Resources. Issue 6 (November 2022) - Harley, Catherine; Curtis, Troy
Video Abstract: Video 1 Equitable healthcare for Indigenous peoples: Development of the "Sharing Circle" Web site to provide a culturally safe method to communicate wound, ostomy, and continence information and resources.